Faecalibacterium duncaniae as a novel next generation probiotic against influenza - Chollet, Loïc; Heumel, Séverine; Deruyter, Lucie; Bouilloux, Fabrice; Delval, Lou; Robert, Véronique; Gevaert, Marie-Hélène; Pichavant, Muriel; Sencio, Valentin; Robil, Cyril; Wolowczuk, Isabelle; Sokol, Harry; et al. (Frontiers in Immunology, 2024)
The gut-lung axis is critical during viral respiratory infections such as influenza. Gut dysbiosis during infection translates into a massive drop of microbially produced short-chain fatty acids (SCFAs). Among them, butyrate is important during influenza suggesting that microbiome-based therapeutics targeting butyrate might hold promises. The butyrate-producing bacterium Faecalibacterium duncaniae (formerly referred to as F. prausnitzii) is an emerging probiotic with several health-promoting characteristics. Supplementation with F. duncaniae notably attenuates gut diseases and inflammation in preclinical models, and clinical studies are ongoing. The potential effect of F. duncaniae supplementation on influenza outcomes has not yet been investigated. Here, we show that oral supplementation of mice with live F. duncaniae (A2-165 or I-4574 strains) five days before infection with influenza A virus was associated with less severe disease, a lower pulmonary viral load, and lower levels of lung inflammation. F. duncaniae supplementation impacted on gut dysbiosis induced by infection, as assessed by 16S rRNA sequencing. Interestingly, F. duncaniae administration was associated with a recovery in levels of SCFAs (including butyrate) in infected animals. The live form of F. duncaniae was more potent that the pasteurized form in improving influenza outcomes. Lastly, F. duncaniae partially protected against secondary (systemic) bacterial infection. We conclude that F. duncaniae might serve as a novel next generation probiotic against acute viral respiratory diseases.